Studies on seed-setting in leguminous plants. I. Peas - Manner, Rolf (Agricultural and Food Science, 1958)
The differences between different genetical materials with regard to the investigated characters have been large. The percentage of fully developed seeds has been smallest for the first seed in the pods on an average (61.0) and much larger for the central seeds (95.2). The corresponding percentage for the last (outermost) seed in each pod was intermediate (82.7). Of the not fully developed seeds, about a fourth part was not at all developed and classified as dead ovules. The relations between the two groups, defective seeds and dead ovules, showed no influence on the position of the seed in the pod. The percentage of pods with all seeds fully developed varied between 14 and 60, and was much dependent on the number of ovules per ovary. The percentage of pod-setting was higher for the low nodes than for the higher ones. The number of ovules per ovary and number of fully developed seeds per pod showed a small tendency to be higher for the lower pods on the stem than for the pods with a high position on the stem. Peduncle length was clearly higher for the lower pods than for the pods with a high position on the stem. Seed weight per pod was considerably higher for pods with a low position on the stem (early flowering) than for pods with a high position on the stem (late flowering) . The length and breadth of the pods, number of ovules per ovary and number of fully developed seeds per pod have on an average been larger for pods from nodes with only one or two pods per node than for pods from nodes with three or more pods per node. The peduncle length was on an average higher for pods on nodes with two pods per node than for pods from nodes with only one pod per node or if the pod number per node was three or even higher. The seed weight per pod was on an average highest for pods developed from nodes with two pods per node and much smaller for pods developed from nodes with three or more pods per node. The seed weight per pod was intermediate for the pods springing from nodes with only one pod. The length of the pods, the breadth of the pods, number of ovules per ovary and number of fully developed seeds were higher for under pods than for over pods. The corresponding numbers for the single pods were lower than for both over and under pods. The peduncle length was considerably smaller for single pods than for over and under pods in the investigated material. Seed weight per pod was higher for under pods than for over pods and single pods.